Slope Stability Analysis Based on Safety Factors on Slope CV. Mutiara Timur in Klampok Village, Tongas District, Probolinggo Regency - Yazid Fanani; Aprilia Dwi Astuti; Andres Kevi Paki (Lembaga Penelititan dan Pengabdian kepada Masyarakat - Institut Teknologi Adhi Tama Suraba, 2021)
CV. Mutiara Timur is a company that is applying for a mining business permit for sirtu commodities in Klampok Village, Tongas District, Probolinggo Regency. The planned mining system is open pit mining using the quarry method. From the results of research in the field obtained rock lithology in the form of topsoil, gravel and sand. Where in the slope design later, the topsoil will be peeled off first. The purpose of slope stability analysis is to determine the geometry of the slope by taking into account the safety factor in order to create safe working conditions. Slope stability analysis on CV. Mutiara Timur using the Bishop method using the Slide v6.0 software. Based on the analysis carried out, the recommendation for slope geometry on a single slope is 4 meters high with a slope of 600 so that the no-load safety factor is 1.350 and the safety factor with load is 1.267. In addition, the slope geometry is obtained on the overall slope, which is a total height of 21 meters with a slope of 380 so that the no-load safety factor is 1.243 and the safety factor with the load is 1.239.